Ethical challenges in reproduction - Kendal, Evie (Henry Stewart Talks, 2024)
Pronatalism, Termination of pregnancy, In Vitro Fertilisation (IVF), Surrogacy, Uterine Transplantation (UTx), Ectogenesis, Synthetic embryo models